Behavioral intention to adopt Islamic banking digital services: A modified UTAUT2 approach - Intan Kusuma Pratiwi (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2024)
Purpose — This research aims to identify the factors that influence customers in using digital Islamic banking services by modifying the UTAUT2 model to include Perceived Credibility and Perceived Risk variables.Method — This research employs a quantitative approach to test and validate the hypotheses formulated. The study population consists of Islamic bank customers in Indonesia. For sample selection, a purposive sampling technique was employed, with the inclusion criterion being that respondents must be Islamic bank customers who have utilized digital Islamic banking services. Data were collected from 373 Islamic bank customers through online Google Forms. The data analysis technique utilized in this research is the Partial Least Squares (PLS) method, conducted using SmartPLS software.Result — The research results indicate that nearly all UTAUT2 variables significantly impact customers' adoption of digital Islamic banking services. Specifically, Perceived Credibility significantly influences customers' adoption of these services, and similarly, Perceived Risk significantly affects customers' adoption of digital Islamic banking services.Contribution — This research introduces a novel framework by modifying the UTAUT2 model, incorporating the variables of Perceived Credibility and Perceived Risk as extensions to the UTAUT2 model.